2020
DOI: 10.1523/eneuro.0521-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Local Design Principles at Hippocampal Synapses Revealed by an Energy-Information Trade-Off

Abstract: Synapses across different brain regions display distinct structure-function relationships. We investigated the interplay of fundamental design constraints that shape the transmission properties of the excitatory CA3-CA1 pyramidal cell connection, a prototypic synapse for studying the mechanisms of learning in the mammalian hippocampus. This small synapse is characterized by probabilistic release of transmitter, which is markedly facilitated in response to naturally occurring trains of action potentials. Based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…However, in the face of a more noisy signal, an optimal signal encoding would require a more robust code that exploits redundancies [38,43,44]. At the synapse, such a robust code could for example be achieved through short-term facilitation [45]. For the future, it will be important to study how such facilitation processes interact with multi-stage vesicle dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the face of a more noisy signal, an optimal signal encoding would require a more robust code that exploits redundancies [38,43,44]. At the synapse, such a robust code could for example be achieved through short-term facilitation [45]. For the future, it will be important to study how such facilitation processes interact with multi-stage vesicle dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Although not explicitly using Pareto theory, several studies have indicated that both extrinsic (synaptic) as well as intrinsic ion channel properties of neurons are concurrently optimal for high energy efficiency (economy) and effective information processing and its biophysical implementation (e.g. [55][56][57][58][59][60][61][62][63][64]).…”
Section: Evolutionary Trade-offs Between Functionality (Effectiveness...mentioning
confidence: 99%